Product complexity assessment for a Proactive-DFA implementation (Simplicity + Simplicity = Complexity) - Rodriguez-Toro, Carlos A. (Cranfield University, 2004)
This thesis presents product complexity as a criterion for the optimisation of product design in the light of an Assembly-Oriented Design and Design for Assembly implementation. It takes a holistic approach to the evaluation of the product architecture by presenting a set of indicators that help examine the product structure at two different levels: Assembly and Component complexity. Assembly complexity assessment is further sub-divided into Structural and Sequence complexity. The latter is a well-known and thoroughly studied area in assembly sequence evaluation, whereas the former gives a novel and original approach to drawing attention to those areas in the product configuration that will consume more resources (i.e. time and tooling required). Component complexity, on the other hand, is sub-divided into manufacturing and process handling/manipulation complexity. The first area has been addressed by the manufacturing analysis section of most Design for Assembly and Manufacturing methodologies, but it has been traditionally addressed as a manual and chart-based evaluation. This is a rigid approach that leaves little room for expansion and has no connection with the product structure. The metrics presented in this work embody a new approach that takes into account the component-to-component interactions and allows the analysis of component shape by extracting its geometry characteristics and comparing them with particular traits of the manufacturing processes available to the designer. Additionally, the metrics presented in this work can be used to make an assessment of the product complexity at a particular point (static complexity) in the development cycle. They can also be registered over a period of time to provide an estimate of the possible consequences of the decisions made during a part of the development cycle (dynamic complexity). By using the methods developed, designers could reduce production costs and increase the reliability of their products.